A wear-resistant hard coating for alloy cutting tools and a preparation method thereof

By applying a wear-resistant hard coating formed by cross-linking modified polyurethane and epoxy-based chitosan on alloy tools, the problem of alloy tools being susceptible to bacterial erosion and fire flammability is solved, and high toughness, antibacterial and flame retardant effects are achieved.

CN119592191BActive Publication Date: 2025-04-15OUYOUGE (DALIAN) CUTTING TOOLS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510139362.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-04-15
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

Existing alloy tool coatings are susceptible to bacterial erosion and fire during long-term use, affecting service life and safety.

Method used

A hard coat with a wear-resistant coating including modified polyurethane, epoxy-based chitosan, titanium dioxide, defoaming agent, film forming additive, wetting agent and water is used to form a coating with high toughness and flame retardancy through the cross-linking of the modified polyurethane and epoxy-based chitosan.

Benefits of technology

It achieves wear resistance, antibacterial and flame retardant effects on alloy tools, extends service life and improves safety.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the field of coating technology, and discloses a wear-resistant hard coating and preparation method thereof applied to alloy cutting tools, the present invention is by adding modified polyurethane, epoxy chitosan, titanium dioxide, BYK 071 defoamer, dipropylene glycol butyl ether film-forming aid, acrylate ammonium salt wetting agent, water into a stirrer, stirring, and obtaining the wear-resistant hard coating applied to alloy cutting tools after terminating. During stirring, the terminal hydroxyl group in the modified polyurethane and the epoxy chitosan undergo a ring-opening reaction, and cross-linking is generated between each other, increasing the compatibility between each other, forming a cross-linked network, and improving the toughness of its coating. The chitosan in modified polyurethane and epoxy chitosan has a good antibacterial effect, and the quaternary ammonium salt in the modified polyurethane also has a good antibacterial effect, and the carbon nanotube therein has good toughness and hardness; The sulfur element in modified polyurethane and epoxy chitosan has a good flame retardant effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, in particular to a wear-resistant hard coating applied to alloy cutting tools and a preparation method thereof. Background Art

[0002] When alloy knives are placed for a long time, they will be corroded by bacteria, which will further corrode the blade and affect their normal use. Therefore, a coating is needed to protect the surface from corrosion. However, when exposed to fire, the flammable coating will also affect its normal use. Therefore, how to avoid this phenomenon is the key to solving the problem. For example, the patent CN113755835A wear-resistant coating and its preparation method, the invention designs alloy elements to obtain a combination of alloy elements that is conducive to increasing the wear resistance of the layer, and the coating has a higher hardness and better wear resistance, but its flame retardant and antibacterial effects are not improved. Summary of the invention

[0003] 1. Technical issues to be resolved

[0004] In view of the deficiencies in the prior art, the present invention provides a wear-resistant hard coating for alloy cutting tools and a preparation method thereof, which has good wear-resistant and antibacterial effects.

[0005] (II) Technical solution

[0006] To achieve the above object, the present invention provides the following technical solution: a wear-resistant hard coating for alloy cutting tools, comprising the following components by weight: 30-50 parts by weight of modified polyurethane, 5-8 parts by weight of epoxy chitosan, 1-3 parts by weight of titanium dioxide, 0.7-1 parts by weight of BYK-071 defoamer, 0.4-0.8 parts by weight of dipropylene glycol butyl ether film-forming aid, 0.6-0.8 parts by weight of ammonium acrylate wetting agent, and 2-5 parts by weight of water;

[0007] The preparation method of the modified polyurethane is:

[0008] (1) Add magnolol and 3-mercaptopropionic acid to a dichloromethane solvent, stir evenly, add benzoin dimethyl ether catalyst, irradiate with ultraviolet light at 25-40° C. for 1-2 h, centrifuge, wash and dry to obtain intermediate 1;

[0009] (2) Add 6-12 parts by weight of intermediate 1 and 0.2-0.3 parts by weight of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide salt to an ethanol solvent, stir at room temperature for 20-35 minutes, continue to add 0.1-0.2 parts by weight of N-hydroxysuccinimide, react in an ice bath for 45-60 minutes to obtain solution A, add 5-8 parts by weight of chitosan hydrochloride to a mixed solution of ethanol and water in a volume ratio of 2:1 to obtain solution B; add solution A to solution B, react at room temperature for 12-18 hours, control the pH to 4.2-5.3, centrifuge after completion, wash with ethanol, and obtain alkenyl chitosan;

[0010] (3) 0.6-0.8 parts by weight of sodium dodecyl sulfate emulsifier, 6-9 parts by weight of alkenyl chitosan, 2-3 parts by weight of vinyl carbon nanotubes, and 4-7 parts by weight of bis(dimethylamino)methylvinylsilane are introduced into the mixture under nitrogen protection, and then 0.2-0.4 parts by weight of azobisisobutyronitrile initiator is added to react at 85-100° C., and the mixture is washed with deionized water and ethanol in turn, and dried to obtain intermediate 2;

[0011] (4) adding chloroethanol and intermediate 2 into N,N-dimethylformamide solvent, reacting at 80-100° C. for 4-6 hours, concentrating after the reaction, washing with ethanol, and obtaining hydroxy quaternized chitosan;

[0012] (5) After removing water from the polyether diol, mix it evenly with hexamethylene diisocyanate, introduce nitrogen, then add dibutyltin dilaurate as a catalyst, react at 50-80°C for 2-4 hours to carry out prepolymerization, then add hydroxyl quaternized chitosan, stir to continue the chain extension reaction, react at 40-55°C for 1-1.5 hours, and after the reaction is completed, cool and discharge to obtain modified polyurethane.

[0013] Preferably, the mass ratio of magnolol, 3-mercaptopropionic acid and benzoin dimethyl ether catalyst in (1) is 1:1.6-2.2:0.01-0.03.

[0014] Preferably, the volume ratio of solution A to solution B in (2) is 1:0.7-1.1.

[0015] Preferably, the reaction time in (3) is 2-4 hours.

[0016] Preferably, the mass ratio of chloroethanol to intermediate 2 in (4) is 2.2-2.6:1.

[0017] Preferably, the mass ratio of polyether diol, hexamethylene diisocyanate, dibutyltin dilaurate catalyst and hydroxy quaternized chitosan in (5) is 1.1-1.3:1:0.01-0.03:0.5-0.8.

[0018] Preferably, the preparation method of the epoxy chitosan is: add 3-6 parts by weight of alkenyl chitosan to N,N-dimethylformamide solvent, stir evenly, add 10-15 parts by weight of hydrogen peroxide aqueous solution thereto, react at 20-30°C for 3-4h, and then perform reduced pressure distillation, filter and dry to obtain epoxy chitosan.

[0019] Preferably, the preparation method of the wear-resistant hard coating for alloy cutting tools is: adding modified polyurethane, epoxy chitosan, titanium dioxide, BYK-071 defoaming agent, dipropylene glycol butyl ether film-forming aid, ammonium acrylate wetting agent, and water into a stirrer, stirring at 25-35°C for 5-10 minutes, and then obtaining the wear-resistant hard coating for alloy cutting tools.

[0020] 3. Beneficial technical effects

[0021] The invention adds modified polyurethane, epoxy chitosan, titanium dioxide, BYK-071 defoamer, dipropylene glycol butyl ether film-forming aid, ammonium acrylate wetting agent and water into a stirrer, and stirs to obtain a wear-resistant hard coating for alloy cutting tools.

[0022] During the stirring process, the terminal hydroxyl groups in the modified polyurethane and the epoxy groups in the epoxy chitosan undergo a ring-opening reaction, which results in cross-linking between them, increasing their compatibility with each other, forming a cross-linking network, and improving the toughness of the coating. The chitosan in the modified polyurethane and epoxy chitosan has a good antibacterial effect, and the quaternary ammonium salt in the modified polyurethane also has a good antibacterial effect. The carbon nanotubes therein have good toughness and hardness; the sulfur element in the modified polyurethane and epoxy chitosan has a good flame retardant effect. DETAILED DESCRIPTION

[0023] The preparation process of vinyl carbon nanotubes refers to the journal "Materials Science and Engineering Plastics", Volume 23, Issue 4, "Surface Vinyl Functionalization of Multi-walled Carbon Nanotubes": 0.3g of multi-walled carbon nanotubes were added to 30mL of 98% concentrated sulfuric acid and 10mL of 70% concentrated nitric acid, refluxed at 140°C for 1h, filtered, and washed. 0.1g of the acidified carbon nanotubes obtained were weighed and dispersed in 15mL of acetone and 15mL of chloroform, 2mL of triethylamine and 5mL of acryloyl chloride were added, and the reaction was carried out at 40°C for 24h. Then 10mL of ethanol was added and stirred for 2h, filtered, and washed to obtain vinyl carbon nanotubes.

[0024] Example 1

[0025] (1) Add magnolol and 3-mercaptopropionic acid to a dichloromethane solvent, stir evenly, then add benzoin dimethyl ether catalyst, wherein the mass ratio of magnolol, 3-mercaptopropionic acid, and benzoin dimethyl ether catalyst is 1:1.6:0.01, irradiate with ultraviolet light at 25°C for 1 h, centrifuge after the irradiation, wash and dry to obtain intermediate 1;

[0026] (2) 6 parts by weight of intermediate 1 and 0.2 parts by weight of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide salt were added to an ethanol solvent, stirred at room temperature for 20 minutes, and then 0.1 parts by weight of N-hydroxysuccinimide was added. The mixture was reacted in an ice bath for 45 minutes to obtain a solution A. 5 parts by weight of chitosan hydrochloride was added to a mixed solution of ethanol and water in a volume ratio of 2:1 to obtain a solution B. Solution A was added to solution B in a volume ratio of solution A to solution B of 1:0.7. The mixture was reacted at room temperature for 12 hours, the pH was controlled to be 4.2, and then centrifuged and washed with ethanol to obtain alkenyl chitosan.

[0027] (3) 0.6 parts by weight of sodium dodecyl sulfate emulsifier, 6 parts by weight of alkenyl chitosan, 2 parts by weight of vinyl carbon nanotubes, and 4 parts by weight of di(dimethylamino)methylvinylsilane were introduced into a nitrogen atmosphere, and then 0.2 parts by weight of azobisisobutyronitrile initiator was added, and the mixture was reacted at 85° C. for 2 h, and then washed with deionized water and ethanol, and dried to obtain intermediate 2;

[0028] (4) adding chloroethanol and intermediate 2 into N,N-dimethylformamide solvent, wherein the mass ratio of chloroethanol to intermediate 2 is 2.2:1, reacting at 80°C for 4 hours, concentrating after the reaction, and washing with ethanol to obtain hydroxy quaternized chitosan;

[0029] (5) After removing water from the polyether diol, mix it evenly with hexamethylene diisocyanate, introduce nitrogen, then drop dibutyltin dilaurate catalyst, react at 50°C for 2 hours to perform prepolymerization, then add hydroxyl quaternized chitosan, wherein the mass ratio of polyether diol, hexamethylene diisocyanate, dibutyltin dilaurate catalyst, and hydroxyl quaternized chitosan is 1.1:1:0.01:0.5, stir to continue chain extension reaction, react at 40°C for 1 hour, and after the reaction is completed, cool and discharge to obtain modified polyurethane;

[0030] (6) Add 3 parts by weight of alkenyl chitosan to N,N-dimethylformamide solvent, stir evenly, then add 10 parts by weight of hydrogen peroxide aqueous solution, react at 20° C. for 3 h, and then distill under reduced pressure, filter and dry to obtain epoxy chitosan;

[0031] (7) 30 parts by weight of modified polyurethane, 5 parts by weight of epoxy chitosan, 1 part by weight of titanium dioxide, 0.7 parts by weight of BYK-071 defoamer, 0.4 parts by weight of dipropylene glycol butyl ether film-forming aid, 0.6 parts by weight of ammonium acrylate wetting agent, and 2 parts by weight of water were added into a stirrer and stirred at 25°C for 5 minutes. After stirring, a wear-resistant hard coating for alloy cutting tools was obtained.

[0032] Example 2

[0033] (1) Add magnolol and 3-mercaptopropionic acid to a dichloromethane solvent, stir evenly, then add benzoin dimethyl ether catalyst, wherein the mass ratio of magnolol, 3-mercaptopropionic acid, and benzoin dimethyl ether catalyst is 1:2.2:0.03, irradiate with ultraviolet light at 40° C. for 2 h, centrifuge after irradiation, wash and dry to obtain intermediate 1;

[0034] (2) 12 parts by weight of intermediate 1 and 0.3 parts by weight of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide salt were added to an ethanol solvent, stirred at room temperature for 35 minutes, and then 0.2 parts by weight of N-hydroxysuccinimide were added. The mixture was reacted in an ice bath for 60 minutes to obtain a solution A. 8 parts by weight of chitosan hydrochloride were added to a mixed solution of ethanol and water in a volume ratio of 2:1 to obtain a solution B. Solution A was added to solution B, wherein the volume ratio of solution A to solution B was 1:1.1, and the mixture was reacted at room temperature for 18 hours. The pH was controlled to be 5.3. After the reaction, the mixture was centrifuged and washed with ethanol to obtain alkenyl chitosan.

[0035] (3) 0.8 parts by weight of sodium dodecyl sulfate emulsifier, 9 parts by weight of alkenyl chitosan, 3 parts by weight of vinyl carbon nanotubes, and 7 parts by weight of di(dimethylamino)methylvinylsilane were introduced into a nitrogen atmosphere for protection, and then 0.4 parts by weight of azobisisobutyronitrile initiator was added, and the mixture was reacted at 100° C. for 4 h, and then washed with deionized water and ethanol in sequence, and dried to obtain intermediate 2;

[0036] (4) adding chloroethanol and intermediate 2 into N,N-dimethylformamide solvent, wherein the mass ratio of chloroethanol to intermediate 2 is 2.6:1, reacting at 100° C. for 6 h, concentrating after the reaction, and washing with ethanol to obtain hydroxy quaternized chitosan;

[0037] (5) After removing water from the polyether diol, mix it evenly with hexamethylene diisocyanate, introduce nitrogen, then add dibutyltin dilaurate catalyst dropwise, react at 80°C for 4 hours to perform prepolymerization, then add hydroxyl quaternized chitosan, wherein the mass ratio of polyether diol, hexamethylene diisocyanate, dibutyltin dilaurate catalyst, and hydroxyl quaternized chitosan is 1.3:1:0.03:0.8, stir to continue chain extension reaction, react at 55°C for 1.5 hours, and after the reaction is completed, cool and discharge to obtain modified polyurethane;

[0038] (6) Add 6 parts by weight of alkenyl chitosan to N,N-dimethylformamide solvent, stir evenly, then add 15 parts by weight of hydrogen peroxide aqueous solution, react at 30° C. for 4 hours, and then distill under reduced pressure, filter and dry to obtain epoxy chitosan;

[0039] (7) 50 parts by weight of modified polyurethane, 8 parts by weight of epoxy chitosan, 3 parts by weight of titanium dioxide, 1 part by weight of BYK-071 defoamer, 0.8 parts by weight of dipropylene glycol butyl ether film-forming aid, 0.8 parts by weight of ammonium acrylate wetting agent, and 5 parts by weight of water were added into a stirrer and stirred at 35°C for 10 minutes. After stirring, a wear-resistant hard coating for alloy cutting tools was obtained.

[0040] Example 3

[0041] (1) Add magnolol and 3-mercaptopropionic acid to a dichloromethane solvent, stir evenly, then add benzoin dimethyl ether catalyst, wherein the mass ratio of magnolol, 3-mercaptopropionic acid, and benzoin dimethyl ether catalyst is 1:1.8:0.02, irradiate with ultraviolet light at 30° C. for 1.5 h, centrifuge after completion, wash, and dry to obtain intermediate 1;

[0042] (2) 10 parts by weight of intermediate 1 and 0.2 parts by weight of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide salt were added to an ethanol solvent, stirred at room temperature for 30 minutes, and then 0.1 parts by weight of N-hydroxysuccinimide was added. The mixture was reacted in an ice bath for 50 minutes to obtain a solution A. 6 parts by weight of chitosan hydrochloride was added to a mixed solution of ethanol and water in a volume ratio of 2:1 to obtain a solution B. Solution A was added to solution B in a volume ratio of solution A to solution B of 1:0.8, and the mixture was reacted at room temperature for 14 hours. The pH was controlled to be 4.8. After the reaction, the mixture was centrifuged and washed with ethanol to obtain alkenyl chitosan.

[0043] (3) 0.7 parts by weight of sodium dodecyl sulfate emulsifier, 8 parts by weight of alkenyl chitosan, 2 parts by weight of vinyl carbon nanotubes, and 6 parts by weight of di(dimethylamino)methylvinylsilane were introduced into a nitrogen atmosphere, and then 0.3 parts by weight of azobisisobutyronitrile initiator was added, and the mixture was reacted at 90° C. for 3 h, and then washed with deionized water and ethanol, and dried to obtain intermediate 2;

[0044] (4) adding chloroethanol and intermediate 2 into N,N-dimethylformamide solvent, wherein the mass ratio of chloroethanol to intermediate 2 is 2.4:1, reacting at 90° C. for 5 h, concentrating after the reaction, and washing with ethanol to obtain hydroxy quaternized chitosan;

[0045] (5) After removing water from the polyether diol, mix it evenly with hexamethylene diisocyanate, introduce nitrogen, then drop dibutyltin dilaurate catalyst, react at 60°C for 3 hours to perform prepolymerization, then add hydroxyl quaternized chitosan, wherein the mass ratio of polyether diol, hexamethylene diisocyanate, dibutyltin dilaurate catalyst, and hydroxyl quaternized chitosan is 1.2:1:0.02:0.6, stir to continue chain extension reaction, react at 45°C for 1 hour, and after the reaction is completed, cool and discharge to obtain modified polyurethane;

[0046] (6) Add 5 parts by weight of alkenyl chitosan to N,N-dimethylformamide solvent, stir evenly, add 12 parts by weight of hydrogen peroxide aqueous solution, react at 25° C. for 3 h, distill under reduced pressure after reaction, filter and dry to obtain epoxy chitosan;

[0047] (7) 40 parts by weight of modified polyurethane, 6 parts by weight of epoxy chitosan, 2 parts by weight of titanium dioxide, 0.8 parts by weight of BYK-071 defoamer, 0.6 parts by weight of dipropylene glycol butyl ether film-forming aid, 0.7 parts by weight of ammonium acrylate wetting agent, and 3 parts by weight of water were added into a stirrer and stirred at 30°C for 7 minutes. After stirring, a wear-resistant hard coating for alloy cutting tools was obtained.

[0048] Comparative Example 1

[0049] Compared with Example 3, this comparative example is different in that polyurethane is used instead of modified polyurethane.

[0050] Comparative Example 2

[0051] Compared with Example 3, this comparative example is different in that chitosan is used instead of epoxy chitosan.

[0052] The flexibility of the coating refers to the national standard GB / T1731; the pencil hardness of the coating layer refers to the national standard GB / T6739; the test results are shown in Table 1.

[0053] Table 1: Membrane performance tests.

[0054] project Flexibility Pencil hardness Example 1 No mesh, cracks or peeling H No scratches Example 2 No mesh, cracks or peeling H No scratches Example 3 No mesh, cracks or peeling H No scratches Comparative Example 1 Slightly textured Minor scratches Comparative Example 2 Slightly textured Minor scratches

[0055] It can be seen from Table 1 that Examples 1-3 of the present invention have better toughness and hardness than Comparative Examples 1-2.

[0056] The limiting oxygen index of the coating was tested using an oxygen index meter, and the combustion level of the coating was tested using a horizontal and vertical combustion instrument. The test results are shown in Table 2.

[0057] Table 2: Flame retardancy test.

[0058] project Limiting oxygen index (%) Combustion level Example 1 30 V-0 Example 2 33 V-0 Example 3 32 V-0 Comparative Example 1 21 V-1 Comparative Example 2 20 V-1

[0059] It can be seen from Table 2 that Examples 1-3 of the present invention have better flame retardant effects than Comparative Examples 1-2.

[0060] Pipette 1 mL of 10 8 CFU / mL of Staphylococcus aureus was added to PBS buffer, and then diluted 10-fold to 10 5 CFU / mL, then add the coating sample (1 cm×1cm×0.2mm), and then culture it in a constant temperature incubator at 37℃ with shaking for 24 h. After culture, add PBS buffer to dilute the bacterial solution 10 times in sequence, and then transfer 0.5 mL of the bacterial solution to the agar medium, and continue to culture it at 37℃ with shaking for 24 h. After culture, count the colonies and count the antibacterial rate.

[0061] Table 3: Antibacterial performance test.

[0062] project Antibacterial rate (%) Example 1 99.3 Example 2 99.7 Example 3 98.4 Comparative Example 1 82.6 Comparative Example 2 81.2

[0063] It can be seen from Table 3 that Examples 1-3 of the present invention have better antibacterial effects than Comparative Examples 1-2.

[0064] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A wear-resistant hard coating for alloy cutting tools, characterized in that: The invention comprises the following components by weight: 30-50 parts by weight of modified polyurethane, 5-8 parts by weight of epoxy chitosan, 1-3 parts by weight of titanium dioxide, 0.7-1 parts by weight of BYK-071 defoamer, 0.4-0.8 parts by weight of dipropylene glycol butyl ether film-forming aid, 0.6-0.8 parts by weight of ammonium acrylate wetting agent, and 2-5 parts by weight of water; The preparation method of the modified polyurethane is: (1) Add magnolol and 3-mercaptopropionic acid to a dichloromethane solvent, stir evenly, add benzoin dimethyl ether catalyst, irradiate with ultraviolet light at 25-40° C. for 1-2 h, centrifuge, wash and dry to obtain intermediate 1; (2) Add 6-12 parts by weight of intermediate 1 and 0.2-0.3 parts by weight of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide salt to an ethanol solvent, stir at room temperature for 20-35 minutes, continue to add 0.1-0.2 parts by weight of N-hydroxysuccinimide, react in an ice bath for 45-60 minutes to obtain solution A, add 5-8 parts by weight of chitosan hydrochloride to a mixed solution of ethanol and water in a volume ratio of 2:1 to obtain solution B; add solution A to solution B, react at room temperature for 12-18 hours, control the pH to 4.2-5.3, centrifuge after completion, wash with ethanol, and obtain alkenyl chitosan; (3) 0.6-0.8 parts by weight of sodium dodecyl sulfate emulsifier, 6-9 parts by weight of alkenyl chitosan, 2-3 parts by weight of vinyl carbon nanotubes, and 4-7 parts by weight of bis(dimethylamino)methylvinylsilane are introduced into the mixture under nitrogen protection, and then 0.2-0.4 parts by weight of azobisisobutyronitrile initiator is added to react at 85-100° C., and the mixture is washed with deionized water and ethanol in turn, and dried to obtain intermediate 2; (4) adding chloroethanol and intermediate 2 into N,N-dimethylformamide solvent, reacting at 80-100° C. for 4-6 hours, concentrating after the reaction, washing with ethanol, and obtaining hydroxy quaternized chitosan; (5) After removing water from the polyether diol, mix it evenly with hexamethylene diisocyanate, introduce nitrogen, then add dibutyltin dilaurate as a catalyst, react at 50-80°C for 2-4 hours to carry out prepolymerization, then add hydroxyl quaternized chitosan, stir to continue the chain extension reaction, react at 40-55°C for 1-1.5 hours, and after the reaction is completed, cool and discharge to obtain modified polyurethane.

2. The wear-resistant hard coating for alloy cutting tools according to claim 1, characterized in that: The mass ratio of magnolol, 3-mercaptopropionic acid and benzoin dimethyl ether catalyst in (1) is 1:1.6-2.2:0.01-0.

03.

3. The wear-resistant hard coating for alloy cutting tools according to claim 1, characterized in that: The volume ratio of solution A to solution B in (2) is 1:0.7-1.

1.

4. The wear-resistant hard coating for alloy cutting tools according to claim 1, characterized in that: The reaction time in (3) is 2-4 hours.

5. The wear-resistant hard coating for alloy cutting tools according to claim 1, characterized in that: The mass ratio of chloroethanol to intermediate 2 in (4) is 2.2-2.6:

1.

6. The wear-resistant hard coating for alloy cutting tools according to claim 1, characterized in that: The mass ratio of polyether diol, hexamethylene diisocyanate, dibutyltin dilaurate catalyst and hydroxy quaternized chitosan in (5) is 1.1-1.3:1:0.01-0.03:0.5-0.

8.

7. The wear-resistant hard coating for alloy cutting tools according to claim 1, characterized in that: The preparation method of the epoxy chitosan is as follows: 3-6 parts by weight of alkenyl chitosan is added to N,N-dimethylformamide solvent, stirred evenly, and then 10-15 parts by weight of hydrogen peroxide aqueous solution is added thereto, reacted at 20-30° C. for 3-4 hours, and then subjected to reduced pressure distillation, filtered and dried to obtain epoxy chitosan.

8. A method for preparing a wear-resistant hard coating for alloy cutting tools according to any one of claims 1 to 7, characterized in that: The preparation method of the wear-resistant hard coating for alloy cutting tools comprises the following steps: adding modified polyurethane, epoxy chitosan, titanium dioxide, BYK-071 defoamer, dipropylene glycol butyl ether film-forming aid, ammonium acrylate wetting agent and water into a stirrer, stirring at 25-35° C. for 5-10 minutes, and obtaining the wear-resistant hard coating for alloy cutting tools after stirring.

Citation Information

Patent Citations

  • Wear-resistant coating and preparation method thereof

    CN113755835A

  • Electrostatic spraying type high abrasion-resistant powder coating and preparation method thereof

    CN106833324A

  • Preparation method for packaging film polyurethane coating layer capable of prolonging food shelf life

    CN109054621A